Pulmonary Expression of TNF- Following Exposure to Mixture of Chlorpyriphos and Cypermethrin with or without Endotoxin - Nazki, Mahwash (Indian Journal of Veterinary Anatomy, 2020)
The present investigations included male albino mice (N=48) aging 6-8 weeks to evaluate the expression of TNF- α in response to chlorpyriphos, cypermethrin and their mixture with or without LPS challenge. The animals were divided into four groups viz. one control and three treatments (N=12). Treatment groups were orally administered with chlorpyriphos @2.76mg/kg, cypermethrin @2mg/kg or mixture dissolved in corn oil for 90 days followed by LPS or NSS challenge @80μl/animal via intranasal route. There was 3.95 folds (p